Barriers and Opportunities for Lecturers’ Career Progression in Vietnam’s Scientific Labour Market - Nguyen, Nu Nguyet Anh; Van Nguyen , Ninh (Journal of Education Culture and Society, 2025)
Aim. This study employs job characteristics theory and human capital theory to establish an analytical framework. Through the lens of Vietnam’s scientific labour market, it examines the relationship between perceived barriers and career advancement opportunities for university lecturers.Methods. This multiple-method approach in the research design entails the gathering of information from a sample mainly comprised of public university lecturers. The analysis of data is performed using PLS-SEM, and the analysis is done through the smartPLS software.Results. The findings show that the important perceived competitive advantage and job performance, which are central to career advancement, are significantly affected by factors including welfare benefits, heavy teaching load, and research funds. These results underscore the necessity of a comprehensive plan that encompasses organisational support and a more accommodating approach to various elements impacting academics in Vietnam’s scientific labour market.Conclusion. The development of such a plan is crucial to foster academic career advancement in Vietnam’s scientific labour market. The strategies must comprise organisational provisions and effective countermeasures to address systemic challenges.Cognitive value. The study aims at understanding and establishing the relationship between structural and organisational factors and individual performance benchmarks and serves as a starting point to inform policy changes in Vietnam education system.